"Even if it's my story it can have your touch": using dialogic processes as an entry point to a culturally responsive writing pedagogy. (2nd January 2020) - Mendelowitz, Belinda; Lazar, Karen
ABSTRACT: We argue that opening a space for dialogic, imaginative writing in the classroom can create entry points for a culturally responsive writing pedagogy (CRWP). We explore how collaborative writing for a pre-existing community digital platform (FundZa) and audience aids the implementation of CRWP in a creative writing course for South African education students. Data from a focus group evaluation show that the course generated a number of new literacy lenses which challenged students to rethink static, monolingual views of language and narrative as well as the kinds of literacies necessary for the creation of a good story. One of the most significant findings entailed a new appreciation of the role of multiple perspectives in the collaborative writing process and moves from a monologic view of writing towards a dialogic view. Many students were encouraged to take imaginative leaps towards unfamiliar cultural contexts and audiences, through peer collaboration, discussion and drafting.